(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2024)
The current study aimed to identify the effect of an interventional treatment program based on cognitive-behavioral therapy to reduce the symptoms of psychological depression in a university student. The case is a girl who studies in the Department of Psychology at the University of Benghazi and comes from a poor family and lives in the outskirts of the city of Al-Marj. She is (21) years old. She suffers from organic or physical diseases, and the researcher relied on observation, interview, and daily records during the treatment sessions to collect data for the current study.